Treatment of obstructive jaundice induced by non-hodgkin lymphoma with EUS-guided transgastric anterograde common bile duct stenting: Technical case report and literature review - Yuan, Lingzhi; Shi, Xiao; Shan, Hongbo; Xiao, Dinghua; Wang, Xiaoyan; Wang, Fen (Frontiers in Surgery, 2023)
Background: Non-Hodgkin lymphoma (NHL) is a rare cause of biliary obstruction. The optimum treatment for these patients is unclear. Lymphoma-associated obstructive jaundice is generally managed with open surgery, Endoscopic retrograde cholangiopancreatography (ERCP), or Percutaneous transhepatic biliary drainage. Here, we present the first description of EUS-guided anterograde common bile duct stenting via the stomach for obstructive jaundice associated with NHL. Patient and methods: : A 58-year-old male patient who had been undergoing chemotherapy for NHL was admitted to our institution for severe obstructive jaundice. The patient's hepatic function indicators were: alanine aminotransferase 211 U/L, aspartate aminotransferase 301 U/L, total bilirubin 485.6 μmol/L, and direct bilirubin 340.2 μmol/L. Abdominal magnetic resonance imaging showed massive lymphomatous lesions filling the peritoneal cavity. Magnetic resonance cholangiopancreatography revealed an external compressive stricture in the superior middle common bile duct and dilation of the intrahepatic and extrahepatic ducts. ERCP was performed unsuccessfully, due to the stricture at the descending junction of the duodenal bulb caused by lymphoma infiltration. So, EUS-guided anterograde common bile duct stenting via the stomach was performed. Results: The patient’s bilirubin level decreased significantly in the postoperative period, and no adverse reaction was observed. Computed tomography showed marked shrinking of the abdominal mass after targeted therapy. Conclusions: Our report suggests that early relief of biliary obstruction may be more beneficial to subsequent chemotherapy when symptoms of lymphoma-associated jaundice are persistently aggravating. Endoscopic ultrasound-guided biliary drainage is a safe, effective and timely alternative approach to treat biliary obstruction when ERCP fails, especially in cases of malignancy caused by extrahepatic bile duct space-occupying lesions.